The investigation of pollution levels in aquaculture - Sansby, Amy (2022)
Aquaculture is currently the fastest growing food sector worldwide, particularly in developing countries such as Kenya and Vietnam. Not only do these countries rely on aquaculture to provide food to their own populations but they also rely on the sector for income through exportation to more developed regions such as the European Union. Therefore, it is crucial that the sector grows in a sustainable way that limits environmental impact and ensures the food is safe for all consumers; helping meet nutritional needs. Therefore, the aims of this study were to assess the quality of aquaculture product from Kenya and aquaculture product that was farmed in Vietnam but purchased in leading UK supermarkets. The study investigated heavy metal and essential element content, microplastic burden, presence of antibiotic residues and the presence of bacteria containing antimicrobial and heavy metal resistance genes. The study found significant differences between both heavy metals and essential elements in wild and farmed fish, different types of fish and between fish farmed in different locations. The study found presence of antibiotic residues in both fish sampled from Kenya and aquaculture product from Vietnam. A number of bacteria were also identified within the aquaculture samples by PCR with the presence of genes for both antibiotic and heavy metal resistance confirmed. The study highlights the need for further work to be carried out in these areas and the importance of monitoring the development of aquaculture.